Population Genomics of the Neotropical Brown Stink Bug, Euschistus heros: The Most Important Emerging Insect Pest to Soybean in Brazil - Zucchi, Maria I.; Cordeiro, Erick M. G.; Wu, Xing; Lamana, Letícia Marise; Brown, Patrick J.; Manjunatha, Shilpa; Viana, João Paulo Gomes; Omoto, Celso; Pinheiro, José B.; Clough, Steven J. (Frontiers in Genetics, 2019)
Recent changes in the soybean management like the adoption of transgenic crops and no-till farming, in addition to the expansion of cultivated areas into new virgin frontiers, are some of the hypotheses that can explain the rise of secondary pests, such as the Neotropical brown stink bug, Euschistus heros, in Brazil. To better access the risk of increased pests like E. heros, and to determine probabilities for insecticide resistance spreading or impact of a new plant variety, it is necessary first to access the local level of the genetic diversity of the pest, and to determine how the species diversity is distributed across different areas and how natural selection is acting upon the natural variation. Using the genotyping by sequencing (GBS) technique, we generated 60,000 single-nucleotide polymorphisms (SNPs) distributed across the E. heros genome. The SNP data can be used to investigate issues related to this emerging pest. We found that E. heros populations presented high levels of genetic diversity with slightly higher values at the central locations in Brazil. Our results also showed strong genetic structure separating northern and southern parts of the range (FST=0.22 p-value=0.000) with a very distinct hybrid zone at the central region. The analyses also suggest the possibility that transcription factors, metabolic enzymes, and GABA channels might play a role in selection. We discuss the implication of this finding to the pest management of emerging pest in agriculture, particular in the context of large areas of monoculture such as soybean and cotton.